Impute-VSS: A comprehensive web-based visualization and simulation suite for comparative data imputation and statistical evaluation - Vartul Shrivastava; Shekhar Shukla (SoftwareX)
In today's technological landscape, where data processing forms the backbone of modeling and predictive analytics, data imputation is crucial in filling missing values within datasets using statistical techniques. However, a notable gap exists in the literature for a toolkit that intuitively offers data imputation. This research aims to bridge the gap by introducing Impute-VSS. This web-based imputation suite offers comparative simulations along with a novel imputation management pipeline for in-depth interpretation of imputation techniques. This manuscript showcases the technical premise of Impute-VSS and emphasises its potential as an inclusive data imputation suite for practitioners and researchers.